Induced biochemical variations in maize parental lines affect the life table and age-specific reproductive potential of Spodoptera frugiperda (J.E. Smith) - Ishwarya Lakshmi, K. S.; Dhillon, Mukesh K.; Mukri, Ganapati; Mahendra, K. R.; Gowtham, K. V.; Tanwar, Aditya K. (Frontiers in Plant Science, 2024)
In recent years, the fall armyworm, Spodoptera frugiperda has rapidly emerged as a global invasive pest, challenging the maize production and leading to considerable economic losses.Developing resistant hybrids is essential for sustainable maize cultivation, which requires a comprehensive understanding of resistance traits and the underlying mechanisms in parental lines. To address this need, the present study aimed to identify the sources of resistance, age and stage-specific effects and role of phytochemicals in plant defense against S. frugiperda in thirty diverse maize parental lines [17 female (A) and 13 male (R) lines]. The study revealed that the larvae fed on maize A-lines CML 565, AI 501, AI 544 and PDIM 639, and R-lines AI 125, AI 542, AI 155, AI 1100 and PML 105 exhibited a reduced intrinsic (r) and finite rate of increase (λ), and net (R0) and gross reproduction rates (GRR); while, increased mean generation time (T) and doubling time (DT). Among these, A-lines CML 565, PDIM 639 and AI 544, and R-lines AI 125, AI 155 and AI 1100 showed higher detrimental effect on reproductive value of S. frugiperda. Aforesaid A-and R-lines were also found with greater increase in insect-induced test phytochemicals compared to other lines, accounting for 25.0 to 72.8% variation in the life table parameters, indicating antibiosis effect on S. frugiperda.Among the test phytochemicals, tannins, CAT, PAL, TAL and APX inflicted greater effect, indicating their role in induced-biochemical defense against S. frugiperda.